Formulation and Evaluation of Montelukast Sodium Oral Dissolving Film - Sharma, Ashish; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2021)
The preliminary batches were planned for the formulation and development of placebos of fast dissolving film by using solvent casting method. Total 10 formulations were prepared by using concentration of polymer i.e pullulan in different proportion. In formulations F5 to F6 various concentration of pullulan were incorporated as well as in other formulation trails taken with different concentration of different natural i.e Sodium alginate, SSG and synthetic i.e HPMC, eudragit to find out best suitable polymer for the film formation. Among all formulations, formulation F5 was found to be satisfactory. The placebos were evaluated for various parameters such as physical appearance, weight variation, thickness, surface pH and disintegration time. F5 formulation came out with best result after various evaluations and so it was further prepared by incorporating Montelukast Sodium API. This formulation was then evaluated for various parameters along with assay, content uniformity and dissolution. The results obtained from the F5 formulation complied with the specifications given for ODF. A batch to batch was also observed after obtaining the results. Further, various batches were prepared with various concentration of PEG-400 and evaluated. It was observed that the batch with the higher concentrations of PEG-400 retarded release of drug from formulation. In vitro release studies showed that the formulation F5 match with the required dissolution profile, the drug release retarded in F1, F2 and F3 formulations due to different concentration of polymer and plasticizer, which did not match with the required dissolution profile. The in vitro release of formulation F5 was found to be most promising as it was in accordance required dissolution profile.